1985
DOI: 10.1073/pnas.82.24.8545
|View full text |Cite
|
Sign up to set email alerts
|

Preimaginal learning as a basis of colony-brood recognition in the ant Cataglyphis cursor

Abstract: In most circumstances, social insects recognize their nestmates. They can discriminate against alien adults and also against alien larvae. Results presented here indicate that the mechanism of colony-brood recognition is acquired in large part during larval life and persists through the metamorphosis into the adult stage. During the first days after emergence of the adult, a weaker form of learning can also occur. These phenomena are discussed in relation to kinship theory. It appears that kin recognition is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
2
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 19 publications
(15 reference statements)
2
74
2
1
Order By: Relevance
“…Slavemaking ants invade colonies of other ant species and transport the pupae back to their own nest. Adults emerging from these pupae react and work for the slave-making species as if it were its own species (Isingrini et al, 1985;Carlin and Schwartz, 1989). The basis for such phenomenon may be olfactory imprinting processes by which the slave ants learn to recognize the slave makers as members of their own species.…”
Section: Early Programmed Learningmentioning
confidence: 99%
“…Slavemaking ants invade colonies of other ant species and transport the pupae back to their own nest. Adults emerging from these pupae react and work for the slave-making species as if it were its own species (Isingrini et al, 1985;Carlin and Schwartz, 1989). The basis for such phenomenon may be olfactory imprinting processes by which the slave ants learn to recognize the slave makers as members of their own species.…”
Section: Early Programmed Learningmentioning
confidence: 99%
“…the capability of sensory systems to elicit behavioral responses to the appropriate type of stimuli) (Lickliter, 2005) is paired with 'immature' forms of prenatal simple learning such as habituation (Schaal, 1988;Shalev et al, 1989;Smotherman and Robinson, 1992;van Heteren et al, 2001). In invertebrates, very few studies have shown prenatal learning and this question is still debated (Isingrini et al, 1985); this constitutes the second aim of this study.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, no study investigated the possible impact of cue learning during early developmental stages on discrimination between adult individuals. Since preimaginal learning of odour cues used in brood recognition has been demonstrated earlier [11,12], here we investigated whether exposure to an alien colony odour during the larval stage might affect nest-mate recognition at the adult stage, thus in a novel adult-adult context. We transferred larvae of the ant Aphaenogaster senilis for a period of time into an 'adoptive colony' of the same species to test whether adult ants, proceeding from these adoptees, would treat differently individuals belonging to the familiar, adoptive colony compared with alien, completely unfamiliar individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Some important insights came from studies on preimaginal olfactory learning in formicine ants. Isingrini et al [11] introduced small and large larvae of Cataglyphis cursor ants in an alien adoptive colony where they developed until the pupal stage; at this point, they were transferred back to their original colony. After eclosion, workers originated from the small larvae group preferred to care for brood belonging to the adoptive colony rather than for their sister brood, but this was not the case for the large larvae group.…”
Section: Introductionmentioning
confidence: 99%